Teachers and students' perceptions of the alignment in a general english curriculum: a case in the Mekong delta - Phạm Như Loan (Trường Đại học Trà Vinh, 2019)
This study aims to achieve two objectives. The first one was to find out the teachers’ perceptions of the alignment between the learning outcomes and teaching and assessment activities in the General English curriculum at the target university. The second aim was to find out the students’ perceptions of the alignment between the learning outcomes and teaching and assessment activities in the General English curriculum at the target university.